Artificial Intelligence Tools and Educational Management for Sustainable Development in Public Rivers State Owned Universities (International Journal of Educational Management, Rivers State University., 2025)
The study examined the relationship between artificial intelligence tools and Educational Management for Sustainable Development in Rivers State Owned Universities. The study adopted a correlational research design. To direct the investigation, two research questions and two hypotheses were formulated to guide the study. The population of the study comprised all 384 level 400 students of Department of Educational Management, Rivers state university and Ignatius Ajuru University of Education. The sample size of 370 students were selected for the study through random sampling techniques. The Researchers developed instruments titled " Artificial Intelligence Questionnaires and Sustainable Development Questionnaires were used to gather data for the study. The reliability coefficient of the study was calculated using crombach's alpha reliability coefficient statistics and the overall reliability coefficient of 0.83 and 0.75 were obtained respectively. Data collected were analysed using pearsons' Product Moment Correlation (PPMC) Statistics. The result obtained showed that artificial intelligence relates with educational Management for sustainable development in Rivers state owned universities. The Researchers recommended that artificial intelligence should be considered as a tool for effective management for sustainable development.